GAMBARAN KEBIASAN MAKAN DAN INDEKS PRESTASI BELAJAR ANAK SD YANG MENGALAMI STUNTING DI SDN 040456 BERASTAGI TAHUN 2017 - Mona Ivana Pintubatu; Albiner Siagian; Zulhaida Lubis (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
Stunting is a chronic malnutrition that the child's growth is not optimal and the body tends to be short. In addition to the incidence of stunting, eating habits are also a factor related to the learning achievement of school children. This study was conducted to describe the eating habits and learning achievement of primary school stunting children in SDN 040456 Berastagi. This study is a descriptive survey research with cross sectional design. The study was conducted by calculating the level of macro and micro nutritional adequacy using the method of food recall 24 hours, assessing the frequency of eating using Food Frequency Questionaire method on 72 stunting children. The Academic achievement seen from the report card last semester prior to this study. Then the data were analyzed descriptively. The results showed stunting children in SDN 040456 Berastagi rarely consume the animal protein that are also rich in minerals.Vegetables and fruits are rarely consumed, although they live in vegetable and fruit-producing areas. Macronutrient adequacy on average of stunting children classified deficit, and also for the sufficiency of micro nutrients. The academic achievement of stunting student in SDN 040456 Berastagi is good although with low nutritional adequacy level. It is recommended that local health workers to provide nutritional counseling of school children, and that the mothers to increase consumption of animal foods, vegetables and fruits to support the growth of childrens height in adolescence. Keywords: Eating Habits, Academic Achievement, Stunting, Primary School Children.